Codesigned Wideband High-Efficiency Filtering SIW Slot Antenna with High Selectivity and Flat Gain Response - Peng Kai Li; Chang Jiang You; Hong Fang Yu; Yu Jian Cheng; Yuan Wang Yang; Jian Hua Deng (International Journal of Antennas and Propagation)
A substrate integrated waveguide (SIW) slot antenna with wideband bandpass filtering performance is proposed in this journal. It consists of a SIW cavity, a transverse slot, three metal posts, and a SMA connector. Three metal posts split the SIW cavity into two TE110-mode resonators. A long nonresonant transverse slot is utilized to realize a half TE110-mode resonator and generate radiation simultaneously so as to reduce the size and release the use of extra radiator. Three in-band resonance poles and a radiation null at both out-of-bands are obtained. A prototype is fabricated and measured. Measured results demonstrate the proposed antenna is with a center frequency of 4.26 GHz, a fractional bandwidth of 9.1%, a high efficiency of 93%, and flat gain response and good skirt selectivity of 270 dB/GHz and 330 dB/GHz for the lower and upper out-of-band, respectively.